Self-assembling and pH-responsive protein nanoparticle as potential platform for targeted tumor therapy - Xu, Zhikun; Zhang, Xiaozhan; Dong, Wang; lv, Huifang; Zuo, Lijie; Zhu, Lifei; Wang, Ruining; Ma, Xia (Frontiers in Molecular Biosciences, 2023)
Frequent injections at high concentrations are often required for many therapeutic proteins due to their short in vivo half-life, which usually leads to unsatisfactory therapeutic outcomes, adverse side effects, high cost, and poor patient compliance. Herein we report a supramolecular strategy, self-assembling and pH regulated fusion protein to extend the in vivo half-life and tumor targeting ability of a therapeutically important protein trichosanthin (TCS). TCS was genetically fused to the N-terminus of a self-assembling protein, Sup35p prion domain (Sup35), to form a fusion protein of TCS-Sup35 that self-assembled into uniform spherical TCS-Sup35 nanoparticles (TCS-Sup35 NP) rather than classic nanofibrils. Importantly, due to the pH response ability, TCS-Sup35 NP well retained the bioactivity of TCS and possessed a 21.5-fold longer in vivo half-life than native TCS in a mouse model. As a result, in a tumor-bearing mouse model, TCS-Sup35 NP exhibited significantly improved tumor accumulation and antitumor activity without detectable systemic toxicity as compared with native TCS. These findings suggest that self-assembling and pH responding protein fusion may provide a new, simple, general, and effective solution to remarkably improve the pharmacological performance of therapeutic proteins with short circulation half-lives.